Search for the doubly charmed baryon Ω+cc - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Science China. Physics, mechanics & astronomy, 2021)
A search for the doubly charmed baryon Ωcc+with the decay mode Ωcc+→ Ξc+K−π+ is performed using proton-proton collision data at a centre-of-mass energy of 13 TeV collected by the LHCb experiment from 2016 to 2018, corresponding to an integrated luminosity of 5.4 fb−1. No significant signal is observed within the invariant mass range of 3.6 to 4.0GeV/c2. Upper limits are set on the ratio R of the production cross-section times the total branching fraction of the Ωcc+→ Ξc+K−π+ decay with respect to the $$Ξ _{cc}^{ + + } → Λ _c^ + {K^ - }{π ^ + }{π ^ + }$$decay. Upper limits at 95% credibility level for R in the range 0.005 to 0.11 are obtained for different hypotheses on the Ωcc+mass and lifetime in the rapidity range from 2.0 to 4.5 and transverse momentum range from 4 to 15 GeV/c.